Ayurvedic Management on Covid-19: A Case Report (AYUSHDHARA, 2022)
Severe acute respiratory syndrome, also known as SARS-Cov-2 or Covid-19, first emerged in march 2020. It has many of the same symptoms as influenza, including a dry cough, headache, body ache, mild increase in body temperature, trouble in breathing, low oxygen levels, nausea, and vomiting. Clinical results of early-stage Covid-19 patients receiving Ayurvedic treatment. Ashwagandha ghan vati and Giloye ghan vati with herbal immune tea or Kahda of Tulsi leaves, ginger, Haldi, Giloye, and Mulaithi, among other ingredients, were used as the first line of treatment. This conventional approach lasted for seven days and included a liquid diet of fresh mosambi and fresh coconut water as well as complete bed rest. The improvement of the Covid -19 afflicted patient's greatest recovery was successfully discovered with the use of a 7-day protocol therapy. Deep breathing exercises, Bhastrika, and Anuloma-Viloma in particular, gave the lungs the vigour they needed to enhance the respiratory system.